PTH-274 Is local excision alone an appropriate option for good clinical responders after chemoradiation in rectal cancers?. (22nd June 2015) - Vallam, KC; Engineer, R; Desouza, A; Patil, P; Saklani, A
Abstract : Introduction: Local excision (LE) is emerging as a treatment option for rectal cancers responding well to chemoradiation. However, LE does not address the mesorectal nodal burden. We aimed to identify factors influencing nodal positivity and subsequently defined a good risk group by including only patients at low risk. Method: Single centre, retrospective analysis of a prospectively maintained database of radically resected rectal cancer patients post neoadjuvant chemoradiation. Results: 524 patients with predominantly low rectal tumours were included. Nodal positivity among ypT0, T1 and T2 groups was 14.7%, 28% and 30%, respectively. The following good risk features were identified: age > 40 years, histologic subtype (classical and mucinous variants) and pathological complete response. 69 patients satisfying all 3 criteria were analysed and the nodal positivity was 10.1% which implies that if we had selected these patients for LE, 1 out of 10 patients would have had unaddressed mesorectal nodes Conclusion: LE cannot be used as a guide to observe patients with complete pathological response as the residual nodal burden will lead to more local recurrences thus impacting survival in an otherwise good prognostic subset. Disclosure of interest: None Declared.